Guiding pharmacist clinical interviews: a safety tool to support the education of patients treated with oral antineoplastic agents. Issue 4 (2nd April 2016) - Ribed, Almudena; Escudero-Vilaplana, Vicente; Romero-Jimenez, Rosa Maria; Iglesias-Peinado, Irene; Herranz-Alonso, Ana; Sanjurjo-Saez, Maria
ABSTRACT: Objective: Oral antineoplastic agents (OAA) lead to new challenges in patient education, monitoring, medication errors, drug interactions, adverse events management, and adherence. The aim is to develop a structured guide supporting pharmacist interviews and onco-hematologic outpatients' education process and to identify the key points that a pharmacist should address in order to increase OAA safety and efficacy. Methods: A literature review was performed and the recommended standards associated with OAA approved by ASCO and MASCC were analyzed. Additionally, a multidisciplinary team was formed to address the key points associated with OAA in clinical practice and to create a useful clinical guide. Results: The multidisciplinary team defined the safety and efficacy key points during patient education and issued recommendations regarding the following items: dose, drug administration, interactions, adverse events, adherence, literacy, quality of life, storage, and handling. A guide was created as a check-list in support of the pharmacist clinical interview. Implications for clinical practice, including adverse events management, drug interactions management, and interventions on adherence were added. Conclusion: This article provides a consensus set of safety recommendations regarding OAA in clinical practice and a well-researched easily implementable support guide to standardize and guarantee quality pharmaceutical care of onco-hematologic outpatients.